AN EXPERIENCE OF THE TREATMENT OF UNSTABLE INTER-TROCHANTERIC FRACTURES WITH THE AO/ASIF PROXIMAL FEMORAL NAIL - Babar, Iqtidar Ullah; Qureshi, Abdur Rehman; Afsar, Sardar Sohail (Journal of Postgraduate Medical Institute, 2011)
Objective: To evaluate the use of local-made proximal femoral nail in the treatment of unstable intertrochantericfemoral fractures.Methodology: This descriptive study was conducted in the Department of Orthopaedics, Lady ReadingHospital, Peshawar, from February 2009 to June 2010. Sixty-two patients with unstable inter-trochantericfemoral fractures, admitted through the Accident & Emergency Department were included in this study. Allpatients were treated with AO/ASIF proximal femoral nail and followed at least till fracture consolidationwhich takes minimum of 6 months.Results: The mean age of the patients was 74.27+ 5.84 years. Two patients died and thirteen patients werelost to follow-up. The results are thus based on a sample of 47 patients. There were no complications in81% (n=38) patients and they achieved fracture consolidation within six months. Three patients underwentrevision surgery due to non-union; two had lag screw penetration into the hip joint, three patientsdeveloped deep wound infection while one patient developed superficial wound infection. The mean preinjury mobility score was 6.8+2.5 while the mean post-operative mobility score was 6.48+2.7 (p=.000).Conclusion: The advantage of immediate stability in difficult and unstable fractures, and the relativelyfew complications serve to recommend the wider use of AO/ASIF proximal femoral nail.